2020
DOI: 10.1126/science.aaz8599
|View full text |Cite
|
Sign up to set email alerts
|

Arctic-adapted dogs emerged at the Pleistocene–Holocene transition

Abstract: Although sled dogs are one of the most specialized groups of dogs, their origin and evolution has received much less attention than many other dog groups. We applied a genomic approach to investigate their spatiotemporal emergence by sequencing the genomes of 10 modern Greenland sled dogs, an ~9500-year-old Siberian dog associated with archaeological evidence for sled technology, and an ~33,000-year-old Siberian wolf. We found noteworthy genetic similarity between the ancient dog and modern sled dogs. We detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 66 publications
6
73
0
Order By: Relevance
“…To investigate the genomic relationships between the Siberian Pleistocene and present-day canids, we assembled a dataset consisting of whole-genome data from 31 Eurasian gray wolves ( Canis lupus ), 21 American gray wolves ( Canis lupus ), 88 dogs ( Canis lupus familiaris ; including 5 ancient dogs), 2 previously published ancient wolves, 3 5 7 coyotes ( Canis latrans ), 3 golden jackals ( Canis aureus ), and an Andean fox ( Lycalopex culpaeus ), which we used as an outgroup ( Table S2 ). Given the varying depth of coverage of the samples, we used two approaches to compare these genomes: we created a dataset with called genotypes for a subset of the samples with a minimum depth of coverage of 10× and a second dataset of haploid data consisting of a consensus sequence for each sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the genomic relationships between the Siberian Pleistocene and present-day canids, we assembled a dataset consisting of whole-genome data from 31 Eurasian gray wolves ( Canis lupus ), 21 American gray wolves ( Canis lupus ), 88 dogs ( Canis lupus familiaris ; including 5 ancient dogs), 2 previously published ancient wolves, 3 5 7 coyotes ( Canis latrans ), 3 golden jackals ( Canis aureus ), and an Andean fox ( Lycalopex culpaeus ), which we used as an outgroup ( Table S2 ). Given the varying depth of coverage of the samples, we used two approaches to compare these genomes: we created a dataset with called genotypes for a subset of the samples with a minimum depth of coverage of 10× and a second dataset of haploid data consisting of a consensus sequence for each sample.…”
Section: Resultsmentioning
confidence: 99%
“… 4 Moreover, ancient genomes from the Yana basin and the Taimyr peninsula provided evidence of at least one extinct wolf lineage that dwelled in Siberia during the Pleistocene. 3 5 Previous studies have suggested that Pleistocene Siberian canids can be classified into two groups based on cranial morphology. Wolves in the first group are most similar to present-day populations, although those in the second group possess intermediate features between dogs and wolves.…”
mentioning
confidence: 99%
“…Whole genome sequencing data from several recent studies 12,16,22,[41][42][43][44][45] , including five ancient dogs, two ancient grey wolves, and 68 modern grey wolves (Supplementary Table 10) were downloaded as aligned (bam format) or unaligned (fastq format) reads. Fastq data was aligned to the dog genome (canFam3.1) using BWA-MEM (v.0.7.17) 34 , after trimming withTrim Galore (v.0.6.4).…”
Section: Haplotype Analysis Of Asip Locus In Ancient Dogs and Wolvesmentioning
confidence: 99%
“…This is consistent with the wide distribution of dominant yellow across modern dog breeds from diverse locations, as well as the dingo (Supplementary Table 9), a feral domesticate introduced to Australia at least 3,500 ybp . Of particular interest is the Zhokov island dog from Siberia 21,22 . Based on a haplotype combination of VP2-HCP4, this sled dog that lived 9,500 years ago exhibited a black back color pattern, allowing it to be easily…”
mentioning
confidence: 99%
“…Snow dogs have a history reaching back over 9500 years in the Artic region (Sinding et al, 2020). The River dogs of Arctic Siberia, revered by the Yukaghir people, transported people and supplies by sled over the snow and ice in winter (Wrangell, 1844).…”
Section: Water Dogsmentioning
confidence: 99%